Nutritional Significance of Macronutrients During the Reproductive Period (Pregnancy And Lactation) - Buranova Gulnoza Boymuratovna , Fayzullayeva Munisakhon Akmalovna, (American Journal of Biology and Natural Sciences, 2026)
The article highlights the role of macronutrients in the healthy diet of pregnant and lactating mothers and the importance of their completeness in the diet. The results were analyzed and ways to address the identified shortcomings were described.